2019
DOI: 10.1038/s41598-019-54520-4
|View full text |Cite
|
Sign up to set email alerts
|

How water-mediated hydrogen bonds affect chlorophyll a/b selectivity in Water-Soluble Chlorophyll Protein

Abstract: The Water-Soluble Chlorophyll Protein (WSCP) of Brassicaceae is a remarkably stable tetrapyrrole-binding protein that, by virtue of its simple design, is an exceptional model to investigate the interactions taking place between pigments and their protein scaffold and how they affect the photophysical properties and the functionality of the complexes. We investigated variants of WSCP from Lepidium virginicum (Lv) and Brassica oleracea (Bo), reconstituted with Chlorophyll (Chl) b, to determine the mechanisms by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Based on their study, this overlap was evident as the excitation energy of S 2 decreases as a result of the axial ligation due to HOMO – 1 destabilization. On the same principle, the heterogeneous protein environment can also modulate the Q y –Q x energy gap and other properties of the chromophores 122 through axial ligation, 78 hydrogen bonding, 123 , 124 macrocyclic ring distortion, 125 , 126 and electrostatic effects. 119 The vibrational modes of Chl a are also fine-tuned in a protein matrix for efficient energy transfer and charge separation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their study, this overlap was evident as the excitation energy of S 2 decreases as a result of the axial ligation due to HOMO – 1 destabilization. On the same principle, the heterogeneous protein environment can also modulate the Q y –Q x energy gap and other properties of the chromophores 122 through axial ligation, 78 hydrogen bonding, 123 , 124 macrocyclic ring distortion, 125 , 126 and electrostatic effects. 119 The vibrational modes of Chl a are also fine-tuned in a protein matrix for efficient energy transfer and charge separation.…”
Section: Resultsmentioning
confidence: 99%
“…The water-soluble chlorophyll protein (WSCP) [1] has emerged in recent years as a promising model system for the investigation of tetrapyrroles in a protein environment [2], by virtue of its structural simplicity [3][4][5], high stability [6][7][8], and capability to be reconstituted in vitro with different tetrapyrroles [9][10][11]. Upon tetramerization of four identical protein monomers, each binding one tetrapyrrole, a homotetrameric complex in which the tetrapyrroles are organized into a "dimer of dimers" configuration is obtained (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of using type II WSCPs for studying spectral tuning is the ability to rigorously modify the protein environment of the Chls by assembling them in vitro with recombinantly expressed proteins [21][22][23][24] . By implementing this strategy, Bednarczyk et al 19 demonstrated a spectral tuning mechanism based on a single-point mutation accounting for two-thirds of the spectral shifts between CaWSCP, and LvWSCP.…”
mentioning
confidence: 99%